THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON MUZAKI LOYALTY - sholihah, nihayatu aslamatis; fahrullah, a'rasy (IJIBE (International Journal of Islamic Business Ethics), 2020)
The aim of this research is to test the effect of customer relationship management (data and information, human resources, process, and technology) towards muzakki loyalty case study Yatim Mandiri Surabaya. this research was conducted with an associative quantitative approach. Number of samples that used in this research is 100 peoples who is active muzakki ini Yatim mandiri Surbaya and use purposive sampling technique. This research use a questionnare that calculates with Likert scale and analyzed with SPSS 23 version. The result of this research indicated that customer relationship management varible has significant effect and positive of muzakki loyalty. Based on the partial test result indicated that customer relationship management has partial effect of muzakki loyalty, and Â based on the coefficient of determination test result, indicated that customer relationship management variable has a big impact as 33,7% of muzakki loyalty.